ANALISIS MINAT PERKEMBANGAN TABUNGAN EMAS PADA PT. PEGADAIAN PERIODE 2019-2021 - Rafi Firas Abdillah (2022)
Investment is the placement of a number of funds today to obtain benefits in the future. Investment activities need to be developed and enhanced for economic development to run smoothly. Pegadaian also provides an alternative investment service for the community. Pegadaian Gold Savings is one of the gold business services available at Pegadaian. With advances in technology that are currently developing, society has become easier in various ways, including the economy, in this case investment. This study aims to see the development of public interest in the currently available Pegadaian Gold Savings service. Investment trends that occur in the community have made the interest in the Pegadaian Gold Savings service quite high. This research shows that the interest in the Pegadaian Gold Savings service is very good, the high interest is due to the good facilities available and the convenience provided by Pegadaian to the public as investors. This shows that public interest in investment has started to develop well and will be higher in the future.